2014
DOI: 10.4269/ajtmh.12-0660
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Serotype 1 Non-Structural Protein NS5 Expression Interferes with HIV Replication in a CD4+ T-Cell Line

Abstract: The NS5 protein expression of certain flaviviruses, such as Dengue virus type 2, West Nile virus, Hepatitis C virus, and GB virus type C, is associated with a reduced in vitro human immunodeficiency virus (HIV) viral load. To evaluate the suppression effect of the dengue virus serotype 1 (DENV1) NS5 protein on HIV replication, a CD4+ T-cell line was transfected with a plasmid that contained the coding sequence of the DENV1 NS5 gene, and later, it was infected with HIV. DENV1 NS5 protein expression suppressed H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Watt and others 8 have reported a reduction in the HIV-1 viral load in an HIV-1-positive patient without HAART treatment who presented with dengue infection in Thailand, and demonstrated that HIV-1 replication was suppressed during the acute phase of the infection. The antiviral mechanism involved has not been described, but previous reports [23][24][25] have shown that DENV-1 and DENV-2 NS5 protein expression inhibits HIV-1 replication in Jurkat CD4 + T cells. This antiviral effect has been associated with an increase in stromal cell-derived factor 1 (SDF-1) cytokine expression and a decrease in CD4 and CXCR4 expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Watt and others 8 have reported a reduction in the HIV-1 viral load in an HIV-1-positive patient without HAART treatment who presented with dengue infection in Thailand, and demonstrated that HIV-1 replication was suppressed during the acute phase of the infection. The antiviral mechanism involved has not been described, but previous reports [23][24][25] have shown that DENV-1 and DENV-2 NS5 protein expression inhibits HIV-1 replication in Jurkat CD4 + T cells. This antiviral effect has been associated with an increase in stromal cell-derived factor 1 (SDF-1) cytokine expression and a decrease in CD4 and CXCR4 expression.…”
Section: Discussionmentioning
confidence: 98%
“…This antiviral effect has been associated with an increase in stromal cell-derived factor 1 (SDF-1) cytokine expression and a decrease in CD4 and CXCR4 expression. 24,25 SDF-1 is the principal ligand for the co-receptor CXCR4 and blocks HIV fusion and entry into the CD4 + T cell. 26 The fact that DENV NS5 protein expression could induce signaling pathway activation through the cell membrane should not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gonzalez et al [36] have reported that coinfection with DV in HIV-1 infected patients resulted in stable CD4+ T cell counts and no acceleration in progression to HIV-1 to AIDS. López-Lemus et al [9] and McLinden et al [10] have shown DV NS5 expression interference with HIV-1 replication in vitro.…”
Section: Mirnas Silence Numerous Viruses In Susceptiblementioning
confidence: 99%
“…These mechanisms include CD4+ receptor modulations by NS4B, NS3 or NS5 proteins [8,10]. In order to determine whether HIV inhibition induced by flavivirus NS5 protein expression is conserved among additional members of the Flaviviridae, Xiang et al [12] characterized the effect of NS5 protein expression for five members of the virus family in CD4 + T cells by plasmids containing the genetic sequences of NS5 DNAs.…”
Section: Seven Members Of Flaviviridae Homologous Host Mirnas Target mentioning
confidence: 99%
See 1 more Smart Citation